HUBUNGAN KECERDASAN EMOSIONAL DAN SPIRITUAL (ESQ) DENGAN NILAI DASAR BUDAYA KERJA PENYULUH PERTANIAN - Husodo, Sapto; Arifin, Miftakhul (Jurnal Ilmu-Ilmu Pertanian, 2011)
This study aimed at revealing the Emotional and Spiritual Quotient (ESQ) and The Based Values of The Performance Culture (BVPC), also the association between The ESQ with The BVPC for The Agricultural Extension Workers (AEWs) This study was descriptive-correlational in nature involving the AEWs and The Extension Center for Agriculture, Fisheries and Forestry Leaders in the District of Sleman, Yogyakarta Province. The data was collected by questionnaire method, and analyzed by descriptive technique and Kendall's Tau Corcelation Test. The result of studies are as follows, (1) the condition of Emotional Quotient(EQ) result was in the low category, (2) the condition of Spiritual Quotient (SQ) result was in the high category, Q) the BVPC result was good, (4) there was no significant correlation between the EQ and the BVPC , and (5) ) there was no significant correlation between the SQ and the BVPC). This implied that the EQ must be increased in order to increase the performance of the AEWs. However, both were not significantly correlated because the performance culture were determined by commitment, especially the leader's commitment